Pedicabs for Urban Transportation in U.S. Cities: Benefits, Challenges, and Regulations. Issue 1 (January 2014) - Conway, Alison; Khallouki, Dounia
Pedicabs are a unique mode providing nonmotorized passenger transportation for short trips in urban areas. Although previously used in the United States primarily for recreational tourism, pedicabs can also serve daily and commuter trips. This paper explores the future role for pedicabs as a mode of urban transportation. Potential benefits of pedicab use in urban areas are identified, as well as challenges that may inhibit operations. Through a review of regulations concerning vehicles, drivers, and operations in New York City and seven other urban areas in the United States, a complicated regulatory environment that reflects an ambiguous understanding of pedicabs and their operations is discussed. Finally, based on findings related to the benefits, challenges, and regulations, the next steps for better understanding the potential for pedicabs as an urban transit mode are presented.